Faktor-Faktor yang Mempengaruhi Fenomena Ketepatwaktuan Publikasi Laporan Keuangan - Anggita Dwiantari, Ni Kadek; Mediatrix Ratna Sari, Maria (E-Jurnal Akuntansi, 2021)
Timeliness is needed to present relevant information. In order for a company to submit its financial reports to the public on time, it must consider the factors that affect the timeliness of the publication of financial reports. This study was done to examine the effect of company size, company age as well as independent commissioners on the timeliness of the publication of financial reports. The research was done at food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange at 2017-2019. The samples were 48 companies and used purposive sampling technique. The technique used was logistic analysis. The result indicated that company size and independent commissioners have a positive effect on the timeliness of the publication of financial reports. Meanwhile the age of the company had no effect on the timeliness of the publication of financial reports. Keywords: Timeliness; Company Size; Company Age; Independent Commissioner.